CSUCI Enrollment Report - Richard Yao:::President::: (2023)
This report provides detailed information in four parts that, taken together answer three questions: (1) What do we know? (2) What are we doing? and (3) What is the plan going forward? From recruitment, admissions, and orientation to the first-year experience, and from removing administrative barriers to continuous improvement of our academic programs, this collaborative, essential work is built on the assumption that addressing our enrollment challenges requires intentional, thoughtful action by cross-divisional teams. Whencombined with the long-term strategic planning already well underway on campus, including new developments in strategic enrollment management, academic master planning, and strategic budget planning, the campus is well-poised to make progress on its most pressing challenges.